Response of plantain to fertilization with P, K and S during the first productive cycle. - Furcal-Beriguete, Parménides (2013)
The objective of thiswork was to evaluate the growth and yield response of thefirst reproductive cycle of plantain (Musa AAB) to the applicationof phosphorus, potassium and sulfur. The study wasestablished in La Fortuna, San Carlos, Costa Rica. The soilwhere the experiments were established is an Inceptisol, formedby volcanic materials, with medium fertility and clayloamtexture. Doses of 0, 125, 250, 375 kg/ha of K2O, 0 and70 kg/ha of P2O5 were applied in trial 1, while in trial 2 wereapplied the same levels of K2O were used, in addition to 0and 30 kg/ha of sulfur (S). The sowing was made in Apriland May of 2008 and 2009, respectively, with corms of thecultivar Curraré “Semi Giant”, with a density of 2.380 and2.223 plants per hectare, in each year. There was no statisticalresponse to K2O doses in the first harvest, but differenceswere obtained in the second trial (2010) for the variablespseudostem girth and height at four and seven months inexperiment 2, and bunch weight, length and thickness of themiddle finger of the second hand. For these three variables,with 375 kg of K2O, the values were: 13.17 kg, 28.81 cmand 62.62 inch treintaidosavo respectively. There was onlyresponse to the use of P2O5 in height and girth at four months(1.32 m 0.39 m), not so for S. The total absorption of K, Pand S at the time of harvest was 237.73, 10.83 and 7.44 kg/ha, respectively.